PENETAPAN PENGAMPUAN UNTUK PENGURUSAN HARTA DAN PERALIHAN HAK ATAS TANAH OLEH HAKIM PENGADILAN AGAMA - Fikri Rahmananda; Destri Nugraheni (Veritas et Justitia, 2025)
This paper analyzes legal reasoning employed by the Religious Court in adjudicating guardianship cases concerning asset management and the transfer of land rights. The research adopts both normative and empirical methods by examining Religious Court regulations on guardianship and conducting interviews with representatives of TASPEN Corp., the Land Office, and Land Deed Officials. The findings show that in certain cases the Court rejected guardianship applications on the grounds that such matters did not fall within the absolute jurisdiction of the Religious Court. In these decisions, judges relied on grammatical interpretation and the argumentum a contrario method of legal reasoning. Conversely, in cases where guardianship was granted, judges based their decisions on Book II of the Supreme Court Guidelines, the principle of Islamic personality, and analogical reasoning, employing various methods of legal interpretation, including authentic, extensive, and systematic interpretation. The study further finds that Religious Court guardianship decisions have legal implications for salary and pension management at TASPEN Corp. However, such decisions do not affect the transfer of land rights unless the Court’s ruling expressly grants permission to the guardian to carry out the transfer.